Asunaprevir Evokes Hepatocytes Innate Immunity to Restrict the Replication of Hepatitis C and Dengue Virus - Tsai, Wei-Lun; Cheng, Jin-Shiung; Shu, Chih-Wen; Lai, Kwok-Hung; Chan, Hoi-Hung; Wu, Chun-Ching; Wu, Jing-Mei; Hsu, Ping-I; Chung, Raymond T.; Chang, Tsung-Hsien (Frontiers in Microbiology, 2017)
Type I Interferon-mediated innate immunity against Flaviviridae, such as Hepatitis C virus (HCV) and Dengue virus (DENV), involves TLR3, RIG-I-like receptor (RLR) and JAK-STAT signal pathways. Asunaprevir is a newly developed HCV protease inhibitor for HCV treatment. Whether asunaprevir activates innate immunity to restrict viral infection is unclear. Thus, this study investigates the effect of asunaprevir on innate immunity and its influence on HCV and DENV infection. Huh 7.5.1, Hep-G2 cells, JFH-1 infection model, and DENV-2 infection were used for the analysis. The activity of asunaprevir-regulated innate immunity signal pathway was assessed with IFN- promoter or IFN-stimulated responsive element (ISRE) reporter assays and immunoblotting of key signal proteins. siRNA-mediated MAVS and TRIF knockdown of cells was performed to assess the effect of asunaprevir-regulated innate immunity against HCV and DENV. Asunaprevir treatment activated ISRE and IFN- promoter-luciferase activities and signaling proteins in the JAK-STAT, MAVS and TRIF pathways in Huh 7.5.1 cells. Asunaprevir-mediated signaling activation was decreased in MAVS-knockdown cells. Importantly, both RNA and protein levels of DENV-2 NS3 were decreased in asunaprevir-treated Huh 7.5.1 and HepG2 cells. In MAVS-knockdown cells, the restrictive effect of asunaprevir on HCV and DENV was attenuated. Our findings reveal an unexpected activity of asunaprevir, the activation of MAVS dependent innate immunity to restrict HCV and DENV infection.